2020
DOI: 10.1016/j.ijscr.2020.08.042
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of recurrent eccrine poroma underlying gluteal abscess

Abstract: Highlights Poroma affects gluteal skin. Trauma is a possible cause. We recommend excision and pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Psoas abscess is classified as primary or secondary. The first one is more common in tropical and in development countries while the second one can be monomicrobial or polymicrobial [ 4 , 5 , [9] , [10] , [11] ].…”
Section: Discussionmentioning
confidence: 99%
“…Psoas abscess is classified as primary or secondary. The first one is more common in tropical and in development countries while the second one can be monomicrobial or polymicrobial [ 4 , 5 , [9] , [10] , [11] ].…”
Section: Discussionmentioning
confidence: 99%
“…No recurrence or malignant transformation was recorded in our study. The unexpected malignant transformation of benign lesions was recorded in several lesions including the AWE, where Song et al found three malignant cases out of 38 AWEs (7.9%) [ 22 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cystoscopic examination reveals papillary growth, tumor-like appearance, diffusely edematous mucosa, submucosal hemorrhage, or erythematous plaques. It is very difficult to distinguish EC from nonspecific cystitis and bladder tumor as the formation of mass lesion is confusing [ 10 , 13 , 14 ]. The most common presentation of patients in our study was dysuria in 77.3% of patients, followed by hematuria in 63.6% then frequency in half of the patients.…”
Section: Discussionmentioning
confidence: 99%